Analisis Pengaruh Kualitas Auditor, Likuditas, Profitabilitas dan Solvabilitas terhadap Opini audit Going Concern pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020 - Endrian Zalogo; Yunus Putra Duho; Arie Pratania Putri (Politeknik Ganesha Medan, 2022)
The purpose of this study was to determine whether the quality of auditors, liquidity, profitability and solvency affect going concern opinions on manufacturing companies listed on the Indonesia Stock Exchange. This type of research is descriptive to understand the characteristics of some variables in certain situations. The data used is secondary data. The population of this survey is 62 manufacturing companies between 2018 and 2020. The sample was extracted using a targeted sampling procedure from a total of 30 companies. Data analysis used descriptive statistical analysis and logistic regression with SPSS 22. The results of logistic regression analysis showed that Auditor Quality had no effect on going concern audit opinion, while liquidity, profitability and solvency had an effect and significant on going concern audit opinion acceptance. The results of the t-test indicate that the significant value of auditor quality on audit opinion is 0.965 > 005 and the t-count value is 0.44 < t-table value of 1.989 shows auditor quality has no effect and is not significant. The results of the t test show that the significant value of liquidity on the audit opinion is 0.030 <0.05 and the t value is 2.222 > the t table value is 1.989. The results of the t-test indicate that the significant value of profitability on audit opinion is 0.000 <0.05 and the t-count value is 4.283 > the t-table value is 1.989. The results of the t-test indicate that the significant value of solvency on the audit opinion is 0.000 <0.05 and the t-count value is 6.862 > the t-table value is 1.989. The results of logistic regression analysis show that Auditor Quality has no effect on going concern audit opinion, while liquidity, profitability and solvency have a significant and significant effect on going concern audit opinion acceptance.